Glucagon Like Peptide 1 and MicroRNA in Metabolic Diseases: Focusing on GLP1 Action on miRNAs - Capuani, Barbara; Pacifici, Francesca; Della-Morte, David; Lauro, Davide (Frontiers in Endocrinology, 2018)
Glucagon like peptide 1 (GLP1) is an incretin hormone released from the enteroendocrine L-type cells of the lower gastrointestinal tract. The active isoforms of GLP1 are rapidly degraded (~ 2 minutes) by protease dipeptidyl peptidase-4 (DPP-4) after their release. Among its functions, GLP1 exerts a pivotal role in regulating glucose and lipid metabolism. In particular, GLP1 increases glucose stimulated insulin secretion, functional pancreatic β-cell mass and decreases glucagon secretion from pancreatic -cells. GLP1 can also be a regulator of lipid and lipoprotein metabolism ameliorating diabetic dyslipidemia, liver steatosis and promoting satiety. Interestingly, it has been found that GLP1 and GLP1 agonists can modulate the expression of different microRNAs (miRNAs), a  22 nucleotides small non-coding RNAs, key modulators of protein expression. In particular, in pancreas, GLP1 increases the expression levels of miRNA-212 and miRNA-132, stimulating insulin secretion. Similarly, GLP1 decreases miR-338 levels, leading to an increase of pancreatic β-cell function, followed by an improvement of diabetic conditions. Moreover, GLP1 modulation of miRNAs expression in the liver regulates hepatic lipid storage. Indeed, GLP1 down-regulates miRNA-34a and miRNA-21 and up-regulates miRNA-200b and miRNA-200c expression in liver, reducing intra hepatic lipid accumulation and liver steatosis. Clinical and pre-clinical studies, discussed in this review, suggest that modulation of GLP1/miRNAs pathway may be a useful and innovative therapeutic strategy for prevention and treatment of metabolic disorders, such as diabetes mellitus and liver steatosis.